Pesticide contamination in indoor home dust: A pilot study of non-occupational exposure in Argentina - Aparicio, Virginia Carolina; Kaseker, Jessica; Scheepers, Paul; Alaoui, Abdallah; Figueiredo, Daniel; Mol, Hans; Silva, Vera; Harkes, Paula; Rheinheimer Dos Santos, Danilo; Geissen, Violette; Costa, Jose Luis (Elsevier, 2025)
Agricultural use of pesticides continues to rise globally. Argentina ranks fifth in use. While pesticides help yields, they also pose risks to human health and the environment. Indoor dust can present high pesticide concentrations, raising concerns about chronic exposure in non-farming households. Studies of pesticides in indoor dust are few worldwide. This pioneering study aimed to identify and/or quantify for the first time pesticide occurrence in indoor dust from urban residences in the Pampas Region, southeast of Buenos Aires Province, Argentina. Pesticide residues in indoor dust from 48 non-agricultural homes in the Pampas plain region were analysed. Study participants completed questionnaires on household demographics, pet ownership, pesticide use, gardening, and habits like leaving shoes outside. We detected 41 out of 49 targeted pesticides, including metabolites and banned compounds. Seven of the 49 tested are dual-use compounds (i.e. pesticide & biocide or veterinary applications). The synergist piperonyl butoxide, the dual-use imidacloprid, and “agricultural only” pesticides carbaryl, glyphosate, and atrazine were detected in all dust samples. Glyphosate, 2,4-D, atrazine, imidacloprid, carbaryl, tetramethrin, and piperonyl butoxide had maximum concentrations exceeding 1, 000 μg kg−1. Complex mixtures of up to 32 residues were found per sample. Questionnaire responses revealed that most participants brought shoes inside (60 %), almost all had pets (93 %), and 51 % had used flea repellents (mainly imidacloprid and fipronil). Approximately 48 % reported pesticide use in the past year, and 19 % reported exposure via their (non-farmer) jobs, e.g., via disinfection and weeding. These findings highlight the prevalence of pesticide residues in residential settings and the need for further research on long-term exposure and risks. Improved tracking of agricultural, household, and mixed-use pesticide applications is crucial, particularly in regions heavily reliant on agriculture.